Acute Esophageal Necrosis: An Uncommon Cause of Hematemesis - Zacharia, George Sarin (OMJ, 2014)
Acute esophageal necrosis or black esophagus is an uncommon clinical entity, diagnosed at the upper gastrointestinal endoscopy with the presence of strikingly black necrotic esophagus. Very often no definite etiology will be identified even though a large list of potential associations has been postulated. Upper gastrointestinal bleeding is the most common clinical presentation, others being epigastric pain, retrosternal chest discomfort and dysphagia. Only about a hundred cases of acute esophageal necrosis have been described in medical literature till this date. We report a case of acute esophageal necrosis in an elderly female who had presented with hematemesis.